Harnessing Earth‐Abundant Lead‐Free Halide Perovskite for Resistive Switching Memory and Neuromorphic Computing - Zijian Feng; Jiyun Kim; Jie Min; Peiyuan Guan; Shuo Zhang; Xinwei Guan; Tingting Mei; Tianxu Huang; Chun‐Ho Lin; Long Hu; Fandi Chen; Zhi Li; et al. (Advanced Electronic Materials)
Abstract Non‐volatile memories are expected to revolutionize a wide range of information technologies, but their manufacturing cost is one of the top concerns researchers must address. This study presents a 1D lead‐free halide perovskite K2CuBr3, as a novel material candidate for the resistive switching (RS) devices, which features only earth‐abundant elements, K, Cu, and Br. To the knowledge, this material is the first low‐dimensional halide perovskite with exceptionally low production costs and minimal environmental impact. Owing to the unique 1D carrier transport along the Cu─Br networks, the K2CuBr3 RS device exhibits excellent bipolar switching behavior, with an On/Off window of 105 and a retention time of over 1000 s. The K2CuBr3 RS devices can also act as artificial synapses to transmit various forms of synaptic plasticities, and their integration into a perceptron artificial neural network can deliver a high algorithm accuracy of 93% for image recognition. Overall, this study underscores the promising attributes of K2CuBr3 for the future development of memory storage and neuromorphic computing, leveraging its distinct material properties and economic benefits.